Chapter Rappresentazioni transcalari, misure e rilievo dello spazio urbano in Leonardo - Romby, Giuseppina Carla (Territori, 2023)
Compositional and functional elements of the innovative architectures by Brunelleschi, Alberti, Michelozzo, Sangallo, seen during its Florentine stay, became for Leonardo a field of experimentation for the development of architectural prototypes, interactions between buildings and urban surroundings, new parameters of functionality and hygiene which define the 'city of Leonardo'. A city made not only of spatial configurations but, above all, of flows of matter and energy those configurations must support, in a game of water and people movements where each design operation recognizes the vital breath of territorial ecosystems.